2020
DOI: 10.1111/coa.13608
|View full text |Cite
|
Sign up to set email alerts
|

Pan‐Scotland tonsillectomy outcomes: A national cross‐sectional study

Abstract: Post-tonsillectomy haemorrhage is the principal complication that can occur following tonsillectomy. The consequences for the patient can include hospital admission, blood transfusion, return to theatre for arrest of haemorrhage and rarely mortality. 1 It is therefore of vital importance to accurately determine the rate of post-tonsillectomy haemorrhage and to identify factors that would decrease its incidence. The National Prospective Tonsillectomy Audit (NPTA), published in 2005, was conducted with the aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 20 publications
0
17
1
Order By: Relevance
“…Another explanation for Australia’s PTH rates for adults may be a potential change in the risk-profile of PTH in patients over time. This may occur as a result of clinicians becoming more stringent with the indication criteria for tonsillectomy, as suggested by Milner et al as a conceivable reason for an increase in national rates of PTH over time as observed in Scotland [ 23 ]. The joint position paper released in July 2008 by the Royal Australasian College of Physicians and The Australian Society of Otolaryngology Head and Neck Surgery provided a national guideline on the indications for tonsillectomy and adenotonsillectomy [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation for Australia’s PTH rates for adults may be a potential change in the risk-profile of PTH in patients over time. This may occur as a result of clinicians becoming more stringent with the indication criteria for tonsillectomy, as suggested by Milner et al as a conceivable reason for an increase in national rates of PTH over time as observed in Scotland [ 23 ]. The joint position paper released in July 2008 by the Royal Australasian College of Physicians and The Australian Society of Otolaryngology Head and Neck Surgery provided a national guideline on the indications for tonsillectomy and adenotonsillectomy [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…PTH rates that are widely considered as benchmarks rates had been derived either from national database studies [14][15][16][19][20][21][22][23][24], large prospective cohort studies [25,26] or national surgery quality registers, conducted in various countries [27,28]. For comparative purposes, only studies that have reported PTH rates defined by severe haemorrhage episodes that required the return to theatre are listed in Table 4.…”
Section: Reference Pth Ratesmentioning
confidence: 99%
“…As such, there is a wide reported rate ranging from 2% to19%. [7][8][9][10][11][12] An accurate insight into the true incidence of PTH and possible risk factors is of paramount importance to accurately counsel patients preoperatively and because of the associated chance of readmission, reoperation, or most significantly, mortality. 13 This study demonstrates a higher rate of postoperative hemorrhage among adults than is typically reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the National Prospective Tonsillectomy Audit in 2003/4 may have missed some patients, the methodology would seem unlikely to miss significant numbers. Milner et al 2 compared routinely data collected using the same methodologies during the two periods. Whilst coding of surgery may be inaccurate, it is hard to see how the significant rise could be anything other than genuine.…”
Section: Rise In Complication Rates For Tonsillectomymentioning
confidence: 99%
“…In the second, Milner et al 2 analysed routinely collected data for adults and children, in a pan‐Scotland study to examine post‐tonsillectomy haemorrhage and return‐to‐theatre rates. A comparison was made between 1998‐2002 and 2013‐2017.…”
Section: Introductionmentioning
confidence: 99%